Suppressor thymus-derived lymphocytes in fungal infection. - Stobo, J D (1976)
Thymus-derived lymphocyte (T-cell) function, as determined in vivo by cutaneous reactivity to several antigens and in vitro by responsiveness to mitogens and antigens, was assessed in 14 patients infected with a variety of fungal organisms. While all patients manifested a normal frequency of peripheral blood T cells, only seven patients reacted to at least one of the antigens used for cutaneous testing and demonstrated normal in vitro T proliferative responses. Three patients exhibited cutaneous anergy but normal in vitro T-cell reactivity while four patients demonstrated persistent anergy and marked in vitro T-cell hyporeactivity which was independent of activity of infection, concurrent medication, or any associated disorders. The marked diminution of in vitro T-cell reactivity noted for these later four patients was not due to a deletion of antigen- or mitogen-reactive cells. Thus, patients' cells which had been initially cultured for 7 days without any mitogenic or antigenic stimulus and which were subsequently washed and recultured with phytohemagglutinin, concanavalin A, or histoplasmin demonstrated a marked increase in their responsiveness. Moreover, this reactivity noted for recultured cells could be suppressed by a nonphagocytic, nonadherent, nonimmunoglobulin-bearing, sheep red blood cell rosette-forming population of cells isolated from the fresh peripheral blood mononuclear cells of the same patient. While these "regulator" T cells were capable of suppressing T-proliferative responses to antigens and mitogens, they did not diminish pokeweed mitogen-induced immunoglobulin synthesis by normal bone marrow-derived lymphocytes. Patients in whom suppressor "T" cells were found were at risk for relapsing, disseminated fungal infection.